2017
DOI: 10.1515/nf-2016-a107
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic top-down influences on the auditory brainstem

Abstract: Abstract:Descending connections are present in many sensory systems and support adaptive information processing. This allows the sensory brain to code a wider range of inputs. A well characterized descending system is the olivo-cochlear cholinergic innervation of the inner ear, which mediates a reduction of the sensitivity of the inner ear upon perception of intense sounds. Because this inhibits the response to background noise, the olivo-cochlear system supports detection of transient sound events. Olivo-coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Several studies showed that the cholinergic system modulates the processing of auditory information in the auditory brainstem, including in the CN (Mulders et al, ; see Künzel & Wagner, for a recent review). Notably neurons in AVCN become more excitable under cholinergic influence (Fujino & Oertel, ; Goyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that the cholinergic system modulates the processing of auditory information in the auditory brainstem, including in the CN (Mulders et al, ; see Künzel & Wagner, for a recent review). Notably neurons in AVCN become more excitable under cholinergic influence (Fujino & Oertel, ; Goyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic inputs affect neurons in the dorsal CN (DCN) (Caspary, Havey, & Faingold, ; Irie, Fukui, & Ohmori, ; Manzoor, Chen, & Kaltenbach, ; He, Wang, Petralia, & Brenowitz, ; Stefanescu & Shore, ) and VCN (Caspary et al, ; Fujino & Oertel, ; Goyer et al, ) via nicotinic and muscarinic acetylcholine receptors. However, even for the well‐studied stellate and bushy neurons in the anteroventral cochlear nucleus (AVCN) the role of the cholinergic modulation in hearing has only been vaguely defined (Künzel & Wagner, ). This is complicated by the fact that cholinergic axons projecting into the CN arise from more than one source: a large portion of cholinergic inputs to the CN are formed by collaterals of the descending olivocochlear bundle (OCB; Ryan, Keithley, Wang, & Schwartz, ; Horváth, Kraus, & Illing, ; Mulders, Winter, & Robertson, ; Guinan, ; Kishan, Lee, & Winer, ; Baashar, Robertson, & Mulders, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic olivo-cochlear neurons include medial olivo-cochlear (MOC) and lateral olivo-cochlear (LOC) neurons. The anatomy and physiology of these efferent circuits has been reviewed in detail ( Ciuman, 2010 ; Künzel and Wagner, 2017 ; Fuchs and Lauer, 2019 ; Romero and Trussell, 2022 ). The efferent synaptic inhibition at cochlear hair cells has been shown to involve α9α10-containing nicotinic receptors ( Elgoyhen et al, 1994 , 2001 ; Taranda et al, 2009 ).…”
Section: Cholinergic Function Is Diverse Along the Ascending Auditory...mentioning
confidence: 99%
“…The effect of the olivo-cochlear reflex on the input–output encoding function of auditory fibers is well-known and has been thoroughly reviewed ( Guinan, 1996 ; Künzel and Wagner, 2017 ). It has also been suggested that activation of the olivo-cochlear reflex could improve signal detection from noisy backgrounds by transiently enhancing acoustic gain in auditory fibers ( Winslow and Sachs, 1988 ; Kawase et al, 1993 ).…”
Section: Cholinergic Function Is Diverse Along the Ascending Auditory...mentioning
confidence: 99%